Gloria E. Magaña-Cota, J. Felipe Charre-Medellín, Raúl Hernández, Jesús Iglesias, Belén Chávez-Galván, Ricardo Bolaños, Ramón Cecaira-Ricoy, Víctor Sánchez-Cordero y Francisco Botello - Magaña-Cota, Gloria E.; Charre-Medellín, Felipe; Hernández, Raúl; Iglesias, Jesús; Chávez-Galván, Belén; Bolaños, Ricardo; Cecaira-Ricoy, Ramón; Sánchez-Cordero, Victor; Botello, Francisco (THERYA, 2010)
We collected three specimens and two photograph records of the hairy-legged vampire bat (Diphylla ecaudata) in the municipalities of Victoria and Xichú. These are the first records of this species in Guanajuato, Mexico. Diphylla ecaudata feeds on avian blood. D. ecaudata is a bat with a long, silky and brown dorsal fur, and white color in the base. It usually inhabits tropical forest, and roosts in caves and abandoned mines. Key words: Chiroptera, Diphylla ecaudata, sanguinivorous, Mexico, Phyllostomidae, first record.